Vasoinhibins regulate the inner and outer blood-retinal barrier and limit retinal oxidative stress - Arredondo Zamarripa, David; Díaz-Lezama, Nundehui; Meléndez García, Rodrigo; Chávez Balderas, Jesús; Adán, Norma; Ledesma-Colunga, Maria G.; Arnold, Edith; Clapp, Carmen; Thebault, Stéphanie (Frontiers in Cellular Neuroscience, 2014)
Vasoinhibins are prolactin fragments present in the retina, where they have been shown to prevent the hypervasopermeability associated with diabetes. Enhanced bradykinin (BK) production contributes to the increased transport through the blood-retina barrier (BRB) in diabetes. Here, we studied if vasoinhibins regulate BRB permeability by targeting the vascular endothelium and retinal pigment epithelium (RPE) components of this barrier. Intravitreal injection of BK in male rats increased BRB permeability. Vasoinhibins prevented this effect, as did the B2 receptor antagonist Hoe-140. BK induced a transient decrease in mouse retinal and brain capillary endothelial monolayer resistance that was blocked by vasoinhibins. Both vasoinhibins and the nitric oxide (NO) synthase inhibitor L-NAME, but not the antioxidant N-acetyl cysteine (NAC), blocked the transient decrease in bovine umbilical vein endothelial cell (BUVEC) monolayer resistance induced by BK; this block was reversed by the NO donor DETANONOate. Vasoinhibins also prevented the BK-induced actin cytoskeleton redistribution, as did L-NAME. BK transiently decreased human RPE (ARPE-19) cell monolayer resistance, and this effect was blocked by vasoinhibins, L-NAME, and NAC. DETANONOate reverted the blocking effect of vasoinhibins. Similar to BK, the radical initiator Luperox induced a reduction in ARPE-19 cell monolayer resistance, which was prevented by vasoinhibins. These effects on RPE resistance coincided with actin cytoskeleton redistribution. Intravitreal injection of vasoinhibins reduced the levels of reactive oxygen species (ROS) in retinas of streptozotocin-induced diabetic rats, particularly in the RPE and capillary-containing layers. Thus, vasoinhibins reduce BRB permeability by targeting both its main inner and outer components through NO- and ROS-dependent pathways, offering potential treatment strategies against diabetic retinopathies.